DARI TRAINER, IMAM IBADAH HINGGA PATRONASE SPIRITUAL : Pelayanan KBIH AL-Hikmah Kepada Calon/ Jamaah Haji di Kabupaten Brebes - Agus Nurhadi (Balai Penelitian dan Pengembangan Agama Semarang, 2008)
Some people stated that the roles of KBIH and its services toward pilgrims are questionable. Several KBIHs have been changed to businessinstitution rather than social institution. There is a kind of comodi.ficationof it. This paper argues, based on field research, that KBIH al-Hikmahhas given satisfied services to pilgrims. The services were not only inthe preparation of pilgrimages (manasik), but also during the pilgrimages in Mecca and and after the pilgrimages in Indonesia. In the preparation of pilgrimages, the role of KBIH was a trainer - making candidates of pilgrims are more understanding and capable for practicingthe ritual. In Mecca, KBIH was not only as guider of long journey. butalso the imam of various rituals of pilgrimages. The role of KBIH hasbecome spiritual patronages ( ecclesiasticum] of pilgrims in the rest oftheir lifes.